“Tabi-Tabi Po”: Exploring A Folk Expression Toward Engkantos Among Generation Z Filipinos - Astorga, John Mark (International Journal of Religion Education and Law, 2025)
Uttering “Tabi-tabi po” is not just a verbal expression habit but a living tradition of many Filipinos. “Tabi-tabi po” literally means “Excuse me”. Filipino people learned to acknowledge and respect the presence of supernatural beings that live with them. Saying ”Tabi-tabi” became a common behavior for Filipino people to respect the engkantos in their surroundings to avoid them getting offended. This study aims to explore this folk expression among Generation Z Filipinos at Granby Colleges of Science and Technology. This study utilized descriptive-qualitive design using semi-structured interviews. The participants of this study were selected using Purposive sampling; the researcher gathered 15 respondents from different provinces such as Cavite, Samar, Bohol, Iloilo and Capiz. In addition, the researcher also added a representation from Metro Manila. This study revealed that most of the respondents still practice “Tabi-tabi po” folk expression and the data shows that they learned this habit from their parents and grandparents. The participants use tabi-tabi po because they acknowledge the existence of engkantos or supernatural beings. Ultimately, The participants also expressed their interest to preserve this expression as part of our cultural heritage. This paper concludes that “Tabi-tabi po” culture is still alive among Generation Z.